The activation energy for Mg acceptor in the Ga-rich InGaN alloys. (February 2017) - Zhao, Chuan-Zhen; Wei, Tong; Chen, Li-Ying; Wang, Sha-Sha; Wang, Jun
Abstract: The activation energy for Mg acceptor in Inx Ga1-x N alloys is investigated. It is found that there are three factors to influence the activation energy for Mg acceptor. One is the stronger dependence of the VBM of Inx Ga1-x N depending on In content than that of the Mg acceptor energy level. The other is the concentration of Mg acceptors. Another is the extending of the valence band-tail states into the band gap. In addition, a model based on modifying the effective mass model is developed. It is found that the model can describe the activation energy for Mg acceptor in the Ga-rich Inx Ga1-x N alloys well after considering the influence of the valence band-tail states. Graphical abstract: Highlights: A model is developed to describe the activation energy for Mg acceptor in the Ga-rich Inx Ga1-x N alloys. The factors influencing on the activation energy for Mg acceptor is analyzed. The valence band-tail states in Ga-rich In x Ga1− x N alloys is relative to the InN clusters.